Kategoria skuteczności prawa w poglądach Leona Petrażyckiego - Stefaniuk, Małgorzata Ewa (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The aim of the discussion herein is to analyse the thought of Leon Petrażycki from the point of view of the role played by the category of efficiency of law law. The study confirmed the research hypothesis that the most important problems raised in Petrażycki's thought are related to the efficiency of law. The issues of law efficiency in Leon Petrażycki's work fall within the scope of legal policy, which was supposed to be the task of consciously determining the directions and goal towards which society is to be led. The main goal, with milestones (instrumental objectives) subordinated to it, is to achieve the ideal of love. For L. Petrażycki, the most important is the motivational efficiency and educational efficiency. On the other hand, the very behaviour compliant with the models included in legal norms is to serve the instrumental purposes, and the currently distinguished efficiency in a broader sense (finitistic) should be recognized taking into account the Petrażycki's ideal of love and the degree of approaching its implementation through legal regulations. Despite love being a fundamental value in human life, we, as a society, are not yet ready to enshrine this value in the Constitution, even though over a hundred years have passed since Leon Petrażycki proclaimed his ideas.